Gestion des risques, lutte contre le terrorisme - Galland, Jean-Pierre (Canadian journal of criminology and criminal justice, 2006)
Examining natural, industrial, health, and other characteristics of modern risk management in industrialized countries and trying to draw from them ideas, techniques, and approaches that could make a useful contribution to the war on terrorism takes researchers down different paths. Following one path, the researcher concludes that the current process of technical democratization in risk management, at least as it is practised in Europe, with the increasingly strong tendency to inform users, citizens, and communities about, and even involve them in, the issues concerned, is incompatible with the propensity to withhold information specific to anti-terrorism activities because releasing it may pose 'a risk.' By following another path, however, it may be possible to transpose to an anti-terrorism context the findings of research on the difficulty of gathering and structuring incident databases with a potential to help prevent disasters, current investigations into the application of lessons learned to ultra-secure systems (nuclear facilities, aviation), and studies on 'organizational reliability.' A third path, that of the distinctive 'enlightened catastrophism' school, leads to simultaneous consideration of both risk-management and anti-terrorism perspectives. (English) [ABSTRACT FROM AUTHOR]